Bárbara Mujica, ed., Shakespeare and the Spanish «Comedia». Translation, Interpretation, Performance. Essays in Honor of Susan L. Fischer - Alejandro García-Reidy (Universitat Autònoma de Barcelona, 2016)
Reseña de Bárbara Mujica, ed., Shakespeare and the Spanish «Comedia». Translation, Interpretation, Performance. Essays in Honor of Susan L. Fischer, Bucknell University Press, Lewisburg, 2013, 298 pp. ISBN 9781611485172.